Repair or observe moderate ischemic mitral regurgitation during coronary artery bypass grafting? Prospective randomized multicenter data - Gulack, Brian C.; Englum, Brian R.; Castleberry, Anthony W.; Daneshmand, Mani A.; Smith, Peter K.; Perrault, Louis P. (Annals of Cardiothoracic Surgery, 2015)
Ischemic mitral regurgitation (MR) is a common occurrence following myocardial infarction and its presence is associated with poor outcomes. The optimal treatment of ischemic MR is a matter of debate, especially for patients with moderate MR severity. Some authors advocate for isolated coronary artery bypass grafting (CABG) for patients with moderate MR, maintaining that reverse ventricular remodeling will reduce MR grade and its associated mortality risk, while others argue that a concomitant mitral valve repair (MVR) or replacement is superior. The Cardiothoracic Surgical Trials Network (CTSN) recently published the 1-year results of the Surgical Treatment of Moderate Ischemic Mitral Regurgitation study, a multicenter, randomized, controlled trial investigating the impact of MVR in addition to CABG compared to CABG alone in the treatment of moderate ischemic MR. Here, we have reviewed previous observational and prospective studies investigating moderate ischemic MR treatment as well as the results of the current CTSN randomized trial. Furthermore, we have summarized the current state of the available evidence and preview potential new information that will become available with planned subgroup analyses and further follow-up of enrolled patients in the recently completed CTSN trial.